(untitled) (Journal of the College of Basic Education, 2022)
With the occurrence of modern developments, technological progress, and massive knowledge inflation in various fields, and with the increasing interest in cognitive strategies and the development of higher thinking skills among male and female students in the various stages of education, many psychological phenomena emerged resulting from their misuse, which lead to a significant impact in influencing the attitudes and behaviors of individuals. The current research aims To identify some behavioral problems (cheating, smoking) among secondary school students and treat them in the light of Islamic education.